2018
DOI: 10.1016/j.pjnns.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of activities of daily living in patients with slowly progressive neuromuscular diseases

Abstract: Slowly progressive neuromuscular diseases include but are not limited to: facioscapulohumeral muscular dystrophy (FSHD) and limb-girdle muscular dystrophy (LGMD), hereditary motor and sensory neuropathy (HMSN) and spinal muscular atrophy type III (SMA3). The purpose of this study is to present an evaluation of basic and complex activities of daily living in patients suffering from these diseases. The study was conducted on a group of 58 Polish patients: 25 patients with HMSN, 19 with LGMD and FSHD and 14 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Physical quality of life (QoL) significantly correlated with disease severity. Adults with SMA perceived limitations in physical functioning and ability to perform daily actions, especially independence in self-feeding, using the restroom and performing transfers, had the greatest impact on general well-being [27,60,[67][68][69][104][105][106][107][108]. One mixed methods study reported that women tended to prioritize the importance of certain activities (e.g.…”
Section: Physical Symptoms and Functionmentioning
confidence: 99%
“…Physical quality of life (QoL) significantly correlated with disease severity. Adults with SMA perceived limitations in physical functioning and ability to perform daily actions, especially independence in self-feeding, using the restroom and performing transfers, had the greatest impact on general well-being [27,60,[67][68][69][104][105][106][107][108]. One mixed methods study reported that women tended to prioritize the importance of certain activities (e.g.…”
Section: Physical Symptoms and Functionmentioning
confidence: 99%